Carceral community in the time of COVID-19: Isolation, adaption, and predation - Fontes, Anthony (Punishment & society, 2023)
State failures to protect prisoners from COVID-19 have made prisons key “hotspots” of infection, particularly in the “new mass carceral zone” of Latin America. In Guatemala, which has the 3rd most overcrowded prison system in the world, such failure was a tragedy foretold. Longstanding hostility towards criminalized populations ensured that prisoners would be left to fend for themselves. This does not mean, however, that we should cast the prison as merely another “zone of abandonment” nor prisoners as helpless victims. Instead, drawing on the concept of “carceral community” and prison ethnography, this article maps how prisoner-leaders, entrepreneurs, extortionists, visitors, and officials navigate the absurd contradictions exposed in the collision between pandemic protection protocols and prison realities. This article explores a disavowed carceral community's efforts to make sense of, adapt to, and leverage the pandemic's constraints in the never-ending struggle to survive, profit from, and project power over and beyond prison life. The informal and the illicit articulate with government pandemic policies to create a volatile but deeply resilient modus vivendi, albeit with dire consequences for the most vulnerable on both sides of prison walls.